2020
DOI: 10.1016/j.system.2019.102166
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vocabulary and viewing comprehension

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Baltova (1994) also reported positive effects of visual clues from videos, and found that learners who had access to audio and video almost doubled the comprehension scores of the audio-only group. A recent study by Durbahn et al (2019) assessed comprehension of a documentary distinguishing between imagery-based, audio-based, and imagery plus audio-based questions. Results showed that, when imagery could be used, learners relied less on the spoken text, whereas for audio-based questions vocabulary knowledge was the factor that played a more important role.…”
Section: Audio-visual Input and Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baltova (1994) also reported positive effects of visual clues from videos, and found that learners who had access to audio and video almost doubled the comprehension scores of the audio-only group. A recent study by Durbahn et al (2019) assessed comprehension of a documentary distinguishing between imagery-based, audio-based, and imagery plus audio-based questions. Results showed that, when imagery could be used, learners relied less on the spoken text, whereas for audio-based questions vocabulary knowledge was the factor that played a more important role.…”
Section: Audio-visual Input and Comprehensionmentioning
confidence: 99%
“…Although still in need of more research, studies including different question types indicate that item type has an effect on comprehension scores and that the presence of on-screen text-or the absence of it-interacts with item type (e.g., Rodgers, 2018b;Shohamy & Inbar, 1991). Another aspect to consider is whether questions are audio based or imagery based because differences have also been found between these two types (Durbahn et al, 2019). Item format-that is, how questions are presented-also deserves attention.…”
Section: Testing Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Captions assist comprehension by helping to break down speech into words and thus facilitating listening and reading comprehension. Crucially, a unique support offered to learners' comprehension by multimodal input is imagery, as noted in the preceding text (e.g., Durbahn et al, 2020;Jones & Plass, 2002). Research into audiovisual input has shown that it can work as a compensatory mechanism especially for low-proficiency learners (e.g., Rodgers, 2016).…”
Section: Language Learning From Multimodal Inputmentioning
confidence: 99%
“…Webb andRodgers (2009a, 2009b) have put forward knowledge of the 3,000 most frequent word families and proper nouns to reach 95% coverage of the input. However, the lexical coverage figures for TV viewing have recently been found to be lower (Durbahn et al, 2020), so the lexical demands are not as high as for reading (knowledge of the 4,000 most frequent word families for adequate comprehension and 8,000 word families for detailed comprehension; Laufer & Ravenhorst-Kalovski, 2010;Nation, 2006). Rodgers and Webb (2011) also established that words are repeated more often in TV programs than in reading, especially in related TV programs, which is beneficial for vocabulary learning.…”
mentioning
confidence: 99%